Social Entrepreneurship and Complex Thinking: Validation of SEL4C Methodology for Scaling the Perception of Achieved Competency - José Carlos Vázquez-Parra; Martina Carlos-Arroyo; Marco Cruz-Sandoval (MDPI AG, 2023)
This article aims to show the validated results of implementing a self-created methodology for developing the perceived achievement of social entrepreneurship competency and how this methodology is equally valid in developing the perceived achievement of complex thinking competency. Presenting a multivariate descriptive statistical analysis, this article offers the results of an educational intervention carried out on a sample group of students from a Mexican university before and after implementing the SEL4C (Social Entrepreneurship Learning for Complexity) methodology (developed by the Interdisciplinary Research Group IRG Reasoning for Complexity R4C at the Institute for the Future of Education IFE of the Tecnologico de Monterrey). It corroborates that the proposed methodology impacts the perceived achievement of social entrepreneurship competency and its sub-competencies and also manages to develop the perception of achievement of the complex thinking competency. This article contributes to the studies associated with the formation of competencies and the social entrepreneurship approach as a valid pedagogical tool for developing transversal skills.